A Green Approach Used for Heavy Metals ‘Phytoremediation’ Via Invasive Plant Species to Mitigate Environmental Pollution: A Review - Irfan Ullah Khan; Shan-Shan Qi; Farrukh Gul; Sehrish Manan; Justice Kipkorir Rono; Misbah Naz; Xin-Ning Shi; Haiyan Zhang; Zhi-Cong Dai; Dao-Lin Du (Plants, 2023)
Heavy metals (HMs) normally occur in nature and are rapidly released into ecosystems by anthropogenic activities, leading to a series of threats to plant productivity as well as human health. Phytoremediation is a clean, eco-friendly, and cost-effective method for reducing soil toxicity, particularly in weedy plants (invasive plant species (IPS)). This method provides a favorable tool for HM hyperaccumulation using invasive plants. Improving the phytoremediation strategy requires a profound knowledge of HM uptake and translocation as well as the development of resistance or tolerance to HMs. This review describes a comprehensive mechanism of uptake and translocation of HMs and their subsequent detoxification with the IPS via phytoremediation. Additionally, the improvement of phytoremediation through advanced biotechnological strategies, including genetic engineering, nanoparticles, microorganisms, CRISPR-Cas9, and protein basis, is discussed. In summary, this appraisal will provide a new platform for the uptake, translocation, and detoxification of HMs via the phytoremediation process of the IPS.